2000
DOI: 10.1002/1096-911x(20001101)35:5<475::aid-mpo6>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Impact of childhood cancer on the mental health of parents

Abstract: We found statistically significant but small differences between the mental health of parents of children with cancer and controls. The small differences suggest that as a group the parents of children with cancer are relatively resilient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 24 publications
7
52
1
1
Order By: Relevance
“…Correlations of social support with psychological distress, helplessness and uncertainty, however, were found in neither fathers nor mothers. Other studies [13,21,22] showed positive correlations between parental emotional functioning and social support, but these findings concern a shorter period after diagnosis than in the present study.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…Correlations of social support with psychological distress, helplessness and uncertainty, however, were found in neither fathers nor mothers. Other studies [13,21,22] showed positive correlations between parental emotional functioning and social support, but these findings concern a shorter period after diagnosis than in the present study.…”
Section: Discussioncontrasting
confidence: 91%
“…Several studies indicate that social support can protect parents from the stress caused by their child's disease and treatment [13,[21][22][23]. In families of a child with cancer, higher scores on family cohesion and adaptability were found to be correlated with lower parental anxiety and fewer parental post-traumatic-stress symptoms [22].…”
Section: Introductionmentioning
confidence: 99%
“…Only five studies had a sample size of 100 children or more [18,19,25,37,55]. The total number of caregivers and children included 2,262 mothers, 1,099 fathers, 65 parents (gender of parent not specified), and 15 other caregivers (e.g., grandparent, stepparent) of 2,600 children with cancer.…”
Section: Resultsmentioning
confidence: 99%
“…The reduction of anxiety, feelings of hopelessness and helplessness improve health status [9]. The study states that the parents of the child with cancer, in general, confirm the relationship between social support and well-being expressed with lower levels of anxiety and depression [10].…”
Section: Introductionmentioning
confidence: 83%